2009
DOI: 10.1096/fj.09-132142
|View full text |Cite
|
Sign up to set email alerts
|

Novel endogenous peptide agonists of cannabinoid receptors

Abstract: Hemopressin (Hp), a 9-residue alpha-hemoglobin-derived peptide, was previously reported to function as a CB(1) cannabinoid receptor antagonist (1) . In this study, we report that mass spectrometry (MS) data from peptidomics analyses of mouse brain extracts identified N-terminally extended forms of Hp containing either three (RVD-Hpalpha) or two (VD-Hpalpha) additional amino acids, as well as a beta-hemoglobin-derived peptide with sequence similarity to that of hemopressin (VD-Hpbeta). Characterization of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
152
0
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 56 publications
3
152
0
12
Order By: Relevance
“…Figure 4D shows the effects of pepcan-12, a 12-amino-acid neuropeptide that is highly expressed in mouse brain (Gomes et al, 2009), on the binding of the orthosteric radioligand agonist [ 3 H]WIN55212-2 at the cannabinoid CB 1 receptor. In contrast to the complete inhibition of radioligand binding mediated by the orthosteric agonist CP55,940, pepcan-12 only partially inhibited specific radioligand binding at saturating concentrations, consistent with limited negative cooperativity (Bauer et al, 2012).…”
Section: Amino Acids and Peptides As Allosteric Modulatorsmentioning
confidence: 99%
“…Figure 4D shows the effects of pepcan-12, a 12-amino-acid neuropeptide that is highly expressed in mouse brain (Gomes et al, 2009), on the binding of the orthosteric radioligand agonist [ 3 H]WIN55212-2 at the cannabinoid CB 1 receptor. In contrast to the complete inhibition of radioligand binding mediated by the orthosteric agonist CP55,940, pepcan-12 only partially inhibited specific radioligand binding at saturating concentrations, consistent with limited negative cooperativity (Bauer et al, 2012).…”
Section: Amino Acids and Peptides As Allosteric Modulatorsmentioning
confidence: 99%
“…The endocannabinoid system is traditionally thought to be modulated by the lipophilic endocannabinoids. However, recent findings indicated that endocannabinoid receptors were also regulated by hemopressin peptides (Heimann et al, 2007;Gomes et al, 2009;Bomar and Galande, 2013). Hemopressin is a nonapeptide derived from the a 1 -chain of rat hemoglobin.…”
Section: Introductionmentioning
confidence: 99%
“…This nonapeptide was reported to function as an endogenous inverse agonist or antagonist of the CB 1 receptor (Heimann et al, 2007;Dodd et al, 2010). Subsequent findings revealed that three related peptides of hemopressin, mouse RVD-hemopressin(a) [(m)RVD-Hpa], mouse VD-hemopressin(a) [(m)VD-Hpa], and mouse VD-hemopressin (b), which were identified in mouse brain extracts, behaved as agonists of cannabinoid receptors with different selectivities toward CB 1 and CB 2 receptors in vitro (Gomes et al, 2009). In the G ai16 -facilitated Ca 21 release assay, both (m)RVD-Hpa and (m)VD-Hpa acted as the CB 1 agonists, whereas mouse VDhemopressin(b) functioned as a cannabinoid agonist at both CB 1 and CB 2 receptors on human embryonic kidney 293 cells coexpressing a chimeric G 16 /G i3 with either the CB 1 or CB 2 cannabinoid receptor (Gomes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, naturally occurring intracellular peptides generated by the proteasome would constitute an as yet poorly understood mechanism by which cells increase their protein network complexity and function (16). Hemopressin, the first intracellular peptide identified using this rationale (19), was shown to have cannabinoid inverse agonist action regulating food intake (20,21), whereas the natural brain hemopressins are secreted and suggested to play an important role as novel endocannabinoids (14,22).…”
mentioning
confidence: 99%